Manajemen Pendidikan Kesetaraan Kejar Paket C Pusat Kegiatan Belajar Masyarakat Amanah ummat Makassar - Harlinda, Harlinda; Madani, Muhlis; Tahir, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine the implementation of the logistics management function at the Office of Population and Civil Registry of Makassar City which focused on four functions, namely the planning function, the budgeting function, the procurement function and the elimination function. This type of research used qualitative descriptive research type that was  not intended testing certain hypotheses but to find a picture of logistics management. As for the results of this study showed that   the planning function indicators were categorized as good because they were structured. The implementation function had been categorized quite well because it was carried out every Saturday and Sunday. Then in organizing, the organizing function was categorized as good, because in essence when a decision was made by deliberation. PKBM Management on Makassar.